Development of Video-Assisted Problem Based Learning Models Worksheet to Improve Students’ Mathematical Problem-Solving Abilities on Junior High School - Hermawan, Deni; Rohaeti, Euis Eti; Sugandi, Asep Ikin ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2025)
The ability to solve mathematical problems is one of the basic skills that is very important for every student to have. This ability not only contributes to the understanding of mathematical concepts, but is also important to support an active and interesting learning process. Therefore, the development of interactive Student Worksheets is very necessary. This study aims to develop worksheet with a Problem Based Learning model supported by video media. The method used in this study is a research design that is divided into two parts, namely planning design and formative evaluation design which includes: 1) expert assessment, 2) individual evaluation, 3) small groups, and 4) proposed trials. The subjects of this study consisted of 40 students at SMPN 2 Cimahi. The data collection techniques used were interviews, documentation studies, questionnaires in the form of scales to validate the feasibility and practicality of the developed teaching materials, in addition, a collection of questions was also used to measure the effectiveness of the developed teaching materials. The data processing process was carried out using quantitative and qualitative methods. The conclusion of this study shows that worksheet is very valid, practical, and effective in improving the mathematical problem-solving abilities of junior high school students. Therefore, this worksheet is worthy of being used in the mathematics learning process.